IMOGERY OF REPORTAGES IN THE BOOK «KILL THE DRAGON. UKRAINION REVOLUTIONS» BY KATARZYNA KWIATKOWSKA-MOSKALEWICZ - Khorob, Solomia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The purpose of the article: to investigatethe the features of the system of images in the reportage of the Polish journalist Katarzyna Kwiatkowska-Moskalewicz, considering the specifics of the journalistic genre and the peculiarities of presenting the topic of revolutions and war. Research methods: hermeneutic, philological and cultural-historical. Research results: in the reports "Kill the dragon. "Ukrainian revolutions" created a whole extensive system of characters-narrators – famous and ordinary people, situations, cities and towns – for a larger-scale implementation of the chosen theme. Scientific novelty: the system of images in the collection of reports by Katarzyna Kwiatkowska-Moskalevich "Kill the Dragon. "Ukrainian revolutions" has not yet become the subject of scientific research in Ukrainian humanitarian science, therefore the results of studying her work, in particular in her journalistic texts, are marked by novelty and relevance. Practical significance of the article: Research materials can be used in the further study of similar ideological and aesthetic problems, as well as supporting materials for journalists when writing their own reports.